(untitled) (Texas Journal of Agriculture and Biological Sciences, 2023)
Bacteria of different species, due to the characteristics of their metabolism, have different abilities to counteract the formation of free radicals and oxidative stress. An indicator reflecting the development of oxidative processes is the antioxidant activity of nutrient media during bacterial cultivation. Goal. Comparative assessment of the antioxidant activity of culture media samples during the cultivation of P. aeruginosa and E. coli.